2016
DOI: 10.1111/febs.13722
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of cellular interacting partners by protein aggregates: implication in a loss‐of‐function pathology

Abstract: Protein misfolding and aggregation are a hallmark of several neurodegenerative diseases (NDs). However, how protein aggregation leads to cytotoxicity and neurodegeneration is still controversial. Emerging evidence demonstrates that sequestration of cellular-interacting partners by protein aggregates contributes to the pathogenesis of these diseases. Here, we review current research on sequestration of cellular proteins by protein aggregates and its relation to proteinopathies. Based on different interaction mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 159 publications
(233 reference statements)
1
57
0
Order By: Relevance
“…However, the absence of significant neuronal abnormalities in tau knock-out mice 9 have suggested that the loss of tau function may be less critical and the gain of toxic function in the process of tau aggregate formation might be the key factor in neurodegeneration. Several recent evidences also suggest that sequestration of cellular interacting partners (proteins or RNA) by protein aggregates could contribute to pathogenesis in a wide spectrum of neurodegenerative diseases 10 . The fact, that the intrinsically unstructured tau protein is capable of interacting with polyanionic cofactors like heparin 11 and cellular RNAs 12 , raises the possibility that the tau protein is also capable of interacting with highly charged macromolecular complexes such as the ribosome.…”
mentioning
confidence: 99%
“…However, the absence of significant neuronal abnormalities in tau knock-out mice 9 have suggested that the loss of tau function may be less critical and the gain of toxic function in the process of tau aggregate formation might be the key factor in neurodegeneration. Several recent evidences also suggest that sequestration of cellular interacting partners (proteins or RNA) by protein aggregates could contribute to pathogenesis in a wide spectrum of neurodegenerative diseases 10 . The fact, that the intrinsically unstructured tau protein is capable of interacting with polyanionic cofactors like heparin 11 and cellular RNAs 12 , raises the possibility that the tau protein is also capable of interacting with highly charged macromolecular complexes such as the ribosome.…”
mentioning
confidence: 99%
“…Our laboratory proposed that protein aggregates sequester cellular interacting partners, resulting in cytotoxicity or neurodegeneration (33). To define whether polyQ‐expanded proteins sequester Ub adaptors into protein aggregates, we applied polyQ‐expanded Htt‐N552 (residues 1–552) and Atx‐3 (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hijacking model implies that sequestration of cellular interacting partners by protein aggregates deteriorates the normal function of the hijacked partners, not only by phase transition or mislocalization but also by reducing their available quantities (27, 33). As hHR23B is able to stabilize the xeroderma pigmentosum group C (XPC) protein functioning in DNA repair (41, 54, 55), we investigated the effect of polyQ‐expanded proteins on the XPC level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain proteins like neurofilaments (Nf) can leak from aggregates-containing neurons and axons undergoing degeneration into extra-cellular fluid, making their way into cerebrospinal fluid (CSF) and blood. In biofluids, proteins like Nf may transiently assemble into circulating protein aggregates (CPA), similarly to what is described for stress granule-like formations in tissues such as brain ( 7 ). Using ultracentrifugation (UC) and low-complexity binders to extract CPA from plasma of healthy individuals, we have recently shown that CPA are enriched with heavy chain neurofilament (NfH) and not with the light and medium isoforms (NfL, NfM).…”
Section: Introductionmentioning
confidence: 79%